Effects of Different Attractants on Growth, Antioxidant Capacity, and Feeding Gene Expression of Procambarus clarkii - Youhai Du; Silei Xia; Wuxiao Zhang; Wenping Yang; Yebing Yu; Zhaoxia Li; Bin Peng; Yude Wang; Bo Liu; Hongyan Tian; Jianhua Ming (Fishes, 2026)
The purpose of this study was to investigate the effects of different feeding-promoting substances added to high plant protein diets on the growth, antioxidant, serum biochemical parameters, immune, and feeding-related genes of Procambarus clarkii. A total of 450 crayfish (3.94 ± 0.03 g) were selected and randomly divided into six groups, with each group consisting of three replicates and 25 crayfish per replicate. The crayfish were fed a basal diet without attractant (control group) and five experimental diets supplemented with 0.4% betaine (BET), 0.4% trimetlylamine oxide (TMAO), 0.4% squid paste (SQU), 0.4% dimethyl-β-propiothetin (DMPT), and 0.4% taurine (TAU). The feeding trial lasted for 6 weeks. The results showed that compared with the control group, the BET, SQU, DMPT, and TAU groups significantly improved in growth performance, weight gain rate, and specific growth rate of crayfish. Compared with the control group, the BET, MTAO, and SQU groups significantly increased hepatopancreas SOD, CAT, and T-AOC. Histological results showed that compared with the control group, all feeding attractant groups could alleviate hepatopancreas tissue damage. Compared with the control group, the TMAO and SQU groups significantly reduced serum GLU content as well as ACP and AKP activities. The results of gene quantitative analysis showed that, compared with the control, TMAO significantly upregulated the expression of tlr, nf-kb, propo, hsp70, and tgf-β, while TAU significantly increased the expression of hsp70, hsp90 and nf-kb genes. Compared with the control group, the expression levels of tor, 4ebp1, and s6k1 in the TMAO group were significantly increased. Compared with the control group, the expression levels of leptin and npy genes in the DMPT group were significantly increased. In summary, the addition of attractants to high plant protein feed has the effects of promoting growth, enhancing antioxidant capacity, improving digestive enzyme activity, alleviating hepatopancreas injury, improving immunity, and promoting feeding.